2014
DOI: 10.3758/s13421-014-0470-6
|View full text |Cite
|
Sign up to set email alerts
|

Order recall in verbal short-term memory: The role of semantic networks

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link:http://openaccess.city.ac.uk/4660/ Link to published version: http://dx.doi.org/10.3758/s13421-014- Copyright and reuse: City Research Online aims to make research outputs of City, University of London available to a wider audience. Copyright and Moral Rights remain with the author(s) and/or copyright holders. URLs from City Research Online may be freely distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
80
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(96 citation statements)
references
References 44 publications
12
80
1
Order By: Relevance
“…This view is also shared by the linguistic account proposed by N. Saffran (1992, 1997), which considers that primacy and recency effects during serial recall are supported by semantic and phonological levels of activation, respectively. This is supported by recent findings showing that serial order recall can also be influenced by semantic variables under some conditions (Acheson, MacDonald & Postle, 2011;Poirier, Saint-Aubin, Mair, Tehan, & Tolan, 2015). Martin and Saffran (1997) also showed that aphasic patients with phonological impairment tend to present reduced recency effects in word/nonword repetition, while patients with semantic impairment tend to present reduced primacy effects.…”
Section: Introductionsupporting
confidence: 57%
“…This view is also shared by the linguistic account proposed by N. Saffran (1992, 1997), which considers that primacy and recency effects during serial recall are supported by semantic and phonological levels of activation, respectively. This is supported by recent findings showing that serial order recall can also be influenced by semantic variables under some conditions (Acheson, MacDonald & Postle, 2011;Poirier, Saint-Aubin, Mair, Tehan, & Tolan, 2015). Martin and Saffran (1997) also showed that aphasic patients with phonological impairment tend to present reduced recency effects in word/nonword repetition, while patients with semantic impairment tend to present reduced primacy effects.…”
Section: Introductionsupporting
confidence: 57%
“…This hypothesis would be interesting to explore in future research. Poirier, Saint-Aubin, Mair, Tehan, and Tolan (2015) report evidence for a contribution from the semantic properties of verbal items to the retention of the serial order of verbal lists. This contrasts with previous research on immediate serial recall, and with some models of serial order that have assumed a long-term memory contribution to memory for items, but not for order.…”
Section: Contributions To This Issuementioning
confidence: 91%
“…A number of studies have investigated semantic-phonological interactions termed semantic binding, the finding that lexico-semantic knowledge affects the nature of phonological representations in VWM and other tasks (e.g., Patterson et al, 1994;Hoffman et al, 2009;Savill et al, 2017). Relatedly, Acheson and colleagues conducted several studies suggesting that phonological and semantic information jointly affect serial order in VWM tasks in a way that would be expected from how information interacts in comprehension and production (Acheson et al, 2010(Acheson et al, , 2011b; see also Poirier et al, 2014). Similarly, Macken et al (2014) investigated the memory implications for prosody, the intonation patterns that span whole phrases and sentences in everyday language use, in VWM tasks.…”
Section: Potential Research Directions and Predictions For A Languagementioning
confidence: 99%